Chandigarh la Main ouverte : d’un urbanisme de plan à un urbanisme de vie - Enrico Chapel; Thierry Mandoul (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This counterpoint to analyses that equate Chandigarh to the excesses of modern planning questions the relationships that the city's designers maintained with Indian civilization, and how certain appropriations by local residents played a part in shaping the initial urban project. The hypothesis is that the urban plan of the new capital of Punjab designed by Le Corbusier and his associates has demonstrated malleability over time, proving itself better able than expected to assimilate the daily or occasional practices of its inhabitants. Further, residents’ active engagement sheds new light on the modernity of Chandigarh, allowing to bring nuances to studies that characterize this urban planning project as based on principles exogenous to Indian culture.